A HISTORICAL OVERVIEW OF TEACHING METHODS: HISTORICAL OVERVIEW OF TEACHING METHODS - Kholkhodjaevich, Zafar (Журнал иностранных языков и лингвистики, 2022)
In spite of the fact that there are several methods and approaches in language teaching, Uzbek teachers are not familiar with most of them. Their knowledge is restricted to certain methods and approaches such as Grammar Translation Method, the Direct Method, and the Audio-lingual Method.